One-Period Coupon Bond Valuation Using the Variance Gamma Model - Hoyyi, Abdul; Abdurakhman; Rosadi, Dedi (Thailand Statistician, 2025)
Bonds issued by companies all have coupons. One-period coupons are issued once and are paid together with the principal amount of the bonds at maturity. Many studies on coupon bond valuations have been carried out using a structural model approach. The model involves the assets of the company. The asset model that is often used is the Black-Scholes-Merton model, which assumes in asset returns with a normal distribution. But in reality, the financial data is not normally distributed and indicates the presence of heavy tails and excess kurtosis. In this study, bond valuation was carried out using the variance gamma (VG) model approach. An empirical study was conducted on bond data from one of the banking companies in Indonesia, namely the Continuous Bond III of Bank CIMB Niaga Phase I 2019 Series B. The bonds were issued on December 19, 2019, with a face value of IDR 1,066,000,000,000 and a maturity date of December 19, 2022. The VG asset model in this study has a mean absolute percentage error (MAPE) value of 1.59 % which gives the conclusion that the asset model is very accurate. The bond valuation shows an expected equity value of IDR 271,071,400,000,000, an expected liability of IDR 31,359,700,000,000, and a default probability of 0. This result indicates that PT Bank CIMB Niaga Tbk is able to fulfill its obligations when the bonds mature.